Iowa Birdline update, October 30, 1989 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1989)
Notes for the Iowa Birdline update for October 30, 1989. Highlights include several good water bird sightings. Epson - sheet feed/flatbed